PENGARUH PELATIHAN DAN PENGEMBANGAN KARYAWAN TERHADAP KOMPETENSI KARYAWAN PADA PDAM TIRTANADI PROVINSI SUMATERA UTARA - Abdurrahim, Abdurrahim; Aprinawati, Aprinawati (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Medan, 2018)
Issues raised in this study is whether there is an effect of employee training on the development of employees, effect of employee training on the competence of employees, the development of employees on the competence of employees at PDAM Tirtanadi North Sumatra either simultaneously or partial. The method used in this study is a correlational method with path analysis that aims to measure the relationship between variables. The total population in this research is 209 employees and sample taken as many as 65 employees. Samples were taken using Arikunto formula. Data analysis techniques are descriptive analysis and inferential statistical analysis. After the data were analyzed with SPSS 22.0, the path analysis obtained by the equation: X2 = 0.380 x1+ 0.925 Îµ1; X3 = 0,296X1 + 0,393X2 +0,818 Îµ2. Hypothesis test shows the results of path coefficient effect of employee training on the development of employees amounted to 0.380 with tcount of 3.258 at a significance level of 0.002, the effect of employee training on the competence of employees amounted to 0,296 with tcount of 2.639 at a significance level of 0.011, influence the development of employee competencies of employees amounted to 0.393 With a value of t count of 3.502 at the level of significance ofÂ 0.001. Thus this hypothesis is accepted that there are pengaru employee training to employee development, there are significant employee training on employee competencies and there is the influence employees competence development of employees.Â Keywords: Employee Training, Employee Development, Employee Competency